2018
DOI: 10.1002/eap.1793
|View full text |Cite
|
Sign up to set email alerts
|

How ecological processes shape the outcomes of stock enhancement and harvest regulations in recreational fisheries

Abstract: Fish stocking and harvest regulations are frequently used to maintain or enhance freshwater recreational fisheries and contribute to fish conservation. However, their relative effectiveness has rarely been systematically evaluated using quantitative models that account for key size- and density-dependent ecological processes and adaptive responses of anglers. We present an integrated model of freshwater recreational fisheries where the population dynamics of two model species affect the effort dynamics of recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 123 publications
(435 reference statements)
2
32
0
Order By: Relevance
“…Adopting such an approach for the Hunder trout would be beneficial for quantifying past and future impact of stocking on genetic variation. It could also aid in developing strategies for enhancing stocking practices to minimise negative genetic and demographic impacts (Araki & Schmid 2010) and for weighing different stocking practices against compensatory mitigation measures (Johnston et al 2018, Arlinghaus et al 2002, Janowitz-Koch et al 2018.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adopting such an approach for the Hunder trout would be beneficial for quantifying past and future impact of stocking on genetic variation. It could also aid in developing strategies for enhancing stocking practices to minimise negative genetic and demographic impacts (Araki & Schmid 2010) and for weighing different stocking practices against compensatory mitigation measures (Johnston et al 2018, Arlinghaus et al 2002, Janowitz-Koch et al 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Populations reduced to critically low numbers have been saved from the brink of extinction by supplementation (Tallmon et al 2004, Hostetler et al 2013, and long-term stocking programmes may be able to ensure the persistence of heavily exploited populations even if they have lost their capacity to reproduce naturally (e.g. through loss of recruitment habitat, Rogers et al 2010, Ziegler et al 2017, Johnston et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of stocking on the presence of species is likely strongest in the early introductory phase when abundant ecological niches are available for colonization. Recent research, however, has shown that once a species is naturally recruiting, stocking with juveniles has no effect on biomass and stock size, e.g., in Esox lucius (Johnston et al in press; Hü hn et al , 2014). This means that once the initial establishment phase is over, continued angler stocking should particularly affect non-naturally recruiting predatory fishes (Johnston et al in press), in our case Anguilla anguilla .…”
Section: Discussionmentioning
confidence: 99%
“…These questions are potentially complex, due for instance to variation in the objectives of stocking programs (e.g. population rehabilitation vs. put-take or put-grow-take) or in the interactions of stocking with habitat suitability (Johnston et al, 2018). Several other fishery system processes are likely avenues for future advances.…”
Section: Frontier 4: Fisheries Systemsmentioning
confidence: 99%